Answer:
a+b+c=7.2111
Explanation:
Let's find the answer but first for clarity we will use the following:
k=a+b+c
Now, using the given equations we have:
(a + b)*(a + b + c) = 41 which is:
(k-c)*k=41 (eq. 1)
(b + c)*(a + b + c) = 38 which is:
(k-a)*k = 38 (eq. 2)
(a + c)*(a + b + c) = 25 which is:
(k-b)*k=25 (eq. 3)
Now, adding all the equations we have:
(k-c)*k + (k-a)*k + (k-b)*k = 41 + 38 + 25 which is:
k*(k-c+k-a+k-b)=104
k*(3k-(a+b+c))=104 but remember that k=a+b+c so:
k*(3k-k)=104
2*k^2=104
k=7.2111
a+b+c=7.2111